Model for rapid assessment of vulnerability of office buildings to blast using SWARA and SMART methods (a case study of swiss re tower) - Nakhaei, Jalal; Bitarafan, Mahdi; Lale Arefi, Shahin; Kapliński, Oleg (Journal of Civil Engineering and Management, 2016)
Accidental and intentional explosions are incidents often destroying buildings and leaving casualties. As a result of these blasts all over the world, demand of safe constructions with less vulnerability to explosions is rising. A large number of office buildings are built each year in many countries, housing large numbers of staff and clients, and due to specific nature and function, activities and services, these buildings are usually centrally located. Their architectural form being vital, therefore the article attempts, firstly, to present indices depicting the building form from the viewpoint of vulnerability to explosion. Secondly, the article presents such indexes as: capability to reduce blast effects, economic factors, simplicity of implementation, relationship among spaces in the crisis condition, and creating the least unusable space. The model of rapid assessment of vulnerability of office buildings forms to blast, SMART (simple multi attribute ranking technique) procedure is used and, applying the SWARA method, the weight of each major index and sub-index is arrived at. The model presented in the paper shows the assessment systems using figures between zero and a hundred, and four levels of vulnerability: weak, medium, good and excellent. The closer the figure to a hundred, the lower the vulnerability of the office building forms to blast. Swiss Re Tower case study was presented in the article rating of vulnerability of this building against explosion. It was found to be equal to 62.11%, and its standing was at medium level.